A comparison of changes in dental students' and medical students' approaches to learning during professional training - Lindemann, Robert; Duek, JodyLee; Wilkerson, LuAnn (European journal of dental education, 2001)
The purposes of this study were 1) to compare the learning approaches of dental students (DS) and medical students (MS) for the Class of 1998 at a single institution at admission and graduation and 2) to determine if their learning approaches changed over the course of their studies. An Approaches to Studying Inventory (ASI) was administered to DS and MS at two times: their first month in school and their last month in school. Means and standard deviations were calculated for three ASI orientations to studying: ‘Meaning’, ‘Reproducing’, and ‘Achieving’. An additional domain referred to as ‘Styles and Pathologies’ identified learning problems. In comparison, DS and MS demonstrated a different pattern of learning approaches at matriculation; however, at graduation these differences were less apparent. Over time, DS reported a decreased use, and MS reported an increased use of the Reproducing orientation bringing them closer together. MS also demonstrated an increased use of the Achieving orientation. The Meaning orientation, which indicates a deep approach to learning, was equivalently used by both groups at entry and remained unaltered.